(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
For the purpose of identifying the risks to which the electronic accounting information system used in the Directorate, the research sample - the Payroll Division (Key Card Management System) was exposed, it became necessary to conduct audits of these systems and conclude by fixing the most important errors to which it was exposed from the beginning of the acquisition of the system, through the operation phase, and ending with the outputs that This has been obtained and requires the existence of a governance management system capable of meeting the requirements to address or reduce these risks. The problem of the research lies in the failure of the higher regulatory bodies to issue special reports for auditing the electronic accounting information system used in the directorate, the research sample, and to include it according to the requirements of the COBIT 2019 framework for governance and management objectives. The research gained its importance from the importance of the external auditor in expressing an impartial technical opinion on the problems faced by the electronic accounting information system resulting from its use by the directorate to carry out its activities and the extent of the reliability of the acquisition of that system and its ability to achieve the desired goals of using those systems in terms of accuracy, efficiency and effectiveness. The research seeks to prepare a report on auditing the electronic accounting information system to achieve the requirements of the COBIT 2019 framework for the salaries item of the research sample, to identify the most important violations or errors to which it was exposed, and according to the use of analytical means for each objective. One of the management and governance objectives of the COBIT 2019 framework, It relied on interviews with management and employees concerned with the electronic accounting information system, as well as employees of the Federal Financial Supervision Bureau, and the research concluded with a set of conclusions, the most important of which is the failure of the higher supervisory and auditing bodies to prepare a report on the transformation of the electronic accounting information system to manual to achieve the ,governance and management objectives of the COBIT framework. 2019 in accordance with the audit guides issued by INTOSAI, which provides guidance on information technology auditing and the use of the Information Technology Audit Guide (WGITA), in addition to not using the COBIT 2019 framework in the process of auditing the electronic accounting information system in the directorate, which helps in identifying the most important risks to which the process was exposed. Transformation and preparing a report explaining these risks and providing appropriate solutions to confront them, The research also presented a set of recommendations, the most prominent of which is the necessity of preparing a report by the highest regulatory bodies on auditing the electronic accounting information system, based on information technology audit guides issued by accredited professional organizations to achieve the requirements of the COBIT 2019 framework and the objectives of governance and management to identify information technology risks and develop solutions to those risks.